Third Party’s Asset Confiscation in Corruption Crime - Supardi Supardi (Yuridika, 2018)
The article is intended to analyze and find the idea of legal philosophy foundation  and develop the concept of proceeds confiscation of corruption crime are enjoyed by a third party, and find the ratio decidendi some of the verdicts related to asset confiscation to a third party without prior seizure, compared with asset confiscation that preceded seizure at the level of investigation. The article found three findings. First, the philosophy foundation of asset confiscation  against third parties is in order to maximize the return of state losses due to corruption. Second, the ratio decidendi verdicts related to assets confiscation to a third party without prior seizure, such that verdicts were not contrary to th laws, human rights and justice. The interpretation of the provisions of Article 19 in conjunction with Article 18 of Law Number 31 Year 1999 on the Eradication of Corruption Criminal as amended by Law Number 20 Year 2001 provides an opportunity asset confiscation  to a third party as long as  the third party is not good manner.  Third, to find advice  for legal reform of the provisions regarding  on confiscation to third party in corruption crime in order  that is not touch  with the third party’s rights as  a subjek of asset confiscation.